2022
DOI: 10.3390/ijms232315388
|View full text |Cite
|
Sign up to set email alerts
|

Placental Transcriptome Profiling in Subtypes of Diabetic Pregnancies Is Strongly Confounded by Fetal Sex

Abstract: The placenta is a temporary organ with a unique structure and function to ensure healthy fetal development. Placental dysfunction is involved in pre-eclampsia (PE), fetal growth restriction, preterm birth, and gestational diabetes mellitus (GDM). A diabetic state affects maternal and fetal health and may lead to functional alterations of placental metabolism, inflammation, hypoxia, and weight, amplifying the fetal stress. The placental molecular adaptations to the diabetic environment and the adaptive spatio–t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The spongiotrophoblast layer consists of trophoblast giant cells, spongiotrophoblast cells, and glycogen cells and is mainly involved in hormone secretion and metabolism [26]. Our study revealed that the spongiotrophoblast area was significantly increased in size at 14.5 dpc, which was not observed in other sFLT1 mouse models [8,14,25]. As hsFLT1 is expressed by cells of the spongiotrophoblast layer, the enlargement of this area might be a consequence of the increased expression in this particular tissue.…”
Section: The Placental Spongiotrophoblast Compartment Is Strongly Aff...mentioning
confidence: 49%
See 1 more Smart Citation
“…The spongiotrophoblast layer consists of trophoblast giant cells, spongiotrophoblast cells, and glycogen cells and is mainly involved in hormone secretion and metabolism [26]. Our study revealed that the spongiotrophoblast area was significantly increased in size at 14.5 dpc, which was not observed in other sFLT1 mouse models [8,14,25]. As hsFLT1 is expressed by cells of the spongiotrophoblast layer, the enlargement of this area might be a consequence of the increased expression in this particular tissue.…”
Section: The Placental Spongiotrophoblast Compartment Is Strongly Aff...mentioning
confidence: 49%
“…Because the hsFLT1 expression is limited to the spongiotrophoblast, hsFLT1 serum concentrations were about three times lower at term compared to previously analyzed hsFLT1 levels in the lentiviral-based placenta-specific sFLT1 mouse models, where hsFLT1 is expressed by the whole placenta [5,8]. The highest sFLT1 serum levels were achieved in mice that systemically overexpress sFLT1 through adenoviral transduction [25] or the transgenic hsFLT1 PE/FGR mouse model established by our group [14,15]. Even if the transgenic hsFLT1/tTA/Tpbpa-Cre mice described here did not reach the high hsFLT1 serum levels that were described previously, our model more specifically simulates the human disease of PE and even the low levels of spongiotrophoblast-derived hsFLT1 are sufficient to show a significant impact on fetal and placental development.…”
Section: Discussionmentioning
confidence: 75%
“…Recent findings have demonstrated that fetal sex may exert a role on maternal insulin sensitivity [ 52 ]. In GDM, the placenta is affected, and different gene expression takes place, with fetal sex playing an important role [ 53 , 54 ]. Moreover, a lipotoxic placenta environment has been established in obese mothers, with enhanced inflammatory and oxidation stress.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of differentially regulated genes and the pathways in which the gene products are involved depends, among other factors, on the disease state, the evaluated disease phenotypes treatments, and/or the tissue or cell type evaluated [28]. Most of the studies focusing on DM found some targets related to the pathogenesis of the disease [28][29][30]. In accordance, we found that DEG genes implicated in pathways known to have a relevant role in DM onset and disease progression, as were numerous genes coding for transcription factors found to be dysregulated.…”
Section: Discussionmentioning
confidence: 99%